Hubungan kecemasan dengan kejadian insomnia pada pasien pre operasi - Sormin, Tumiur; Puri, Anita; Azzahra, Ulfa (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2022)
Background: Some operations cause a certain level of anxiety that is different for each person, such as major surgery that requires general anesthesia, making patients feel anxious with a percentage of 20-50% anxiety, excessive fear and sleep disturbances. While secondary surgery only requires local anesthesia for a short time with a percentage of 10-30% characterized by feelings of nervousness, anxiety, worry and sleep disturbances. A survey conducted at a hospital in the United States showed that stimuli that can interfere with sleep in the hospital include difficulty in finding a comfortable body position (62%), pain (58%), anxiety (30%), fear (25 %), and a new environment (18%), uncomfortable bed (10%). Purpose: The purpose of this study was to determine the relationship between anxiety and the incidence of insomnia in preoperative patients at Bhayangkara Polda Lampung Hospital in 2021. Methods: This type of research is a quantitative research with a cross sectional approach. The sampling technique used a purposive sampling with non random sampling, a sample of 45 respondents. The analysis test in this study used the Chi-Square test. This type of research is a quantitative research with a cross sectional approach. The sampling technique used a purposive sampling technique with non-random sampling, a sample of 45 respondents. The analysis test in this study used the Chi-Square test. Results: The results showed that there was a significant relationship between anxiety and the incidence of insomnia. It can also be interpreted that anxiety can affect the incidence of insomnia in preoperative patients and obtained p-value (0.05), Ho is rejected, there is a relationship. Conclusion: There is a relationship between anxiety and the incidence of insomnia in preoperative patients at Bhayangkara Hospital Polda Lampung in 2021. Pendahuluan: Beberapa tindakan operasi menyebabkan tingkat kecemasan tertentu yang berbeda pada setiap orang, seperti operasi besar yang membutuhkan anastesi umum membuat pasien merasa cemas dengan persentase 20-50% kecemasan, ketakutan berlebihan dan gangguan tidur. Sedangkan operasi sekunder hanya butuh anastesi lokal dengan waktu singkat dengan persentase 10-30% ditandai dengan perasaan gugup, gelisah, khawatir dan juga dapat mengalami gangguan tidur. Sebuah survei yang dilakukan di sebuah rumah sakit di Amerika Serikat menunjukkan bahwa rangsangan yang dapat mengganggu tidur di rumah sakit antara lain kesulitan dalam menemukan posisi tubuh yang nyaman (62%), nyeri (58%), kecemasan (30%), ketakutan (25%), dan lingkungan baru (18%), tempat tidur tidak nyaman (10%). Tujuan: Tujuan dari penelitian ini adalah untuk mengetahui hubungan kecemasan dengan kejadian insomnia pada pasien pre operasi di RS Bhayangkara Polda Lampung Tahun 2021. Metode: Jenis penelitian ini adalah penelitian kuantitatif dengan pendekatan cross sectional. Teknik sampling menggunakan teknik purposive sampling dengan non rendom sampling, sampel sebanyak 45 responden. Uji analisis dalam penelitian ini menggunakan uji Chi-Square. Hasil: Hasil penelitian menunjukkan terdapat hubungan yang signifikan antara kecemasan dengan kejadian insomnia. Hal ini dapat diartikan pula bahwa kecemasan dapat mempengaruhi kejadian insomnia pada pasien pre operasi dan didapatkan p-value ≤ α (0,05), Ho ditolak maka ada hubungan. Simpulan: Ada hubungan kecemasan dengan kejadian insomnia pada pasien pre operasi di RS Bhayangkara Polda Lampung Tahun 2021.